2019
DOI: 10.1016/j.yexcr.2019.111503
|View full text |Cite
|
Sign up to set email alerts
|

Furin inhibition prevents hypoxic and TGFβ-mediated blood-brain barrier disruption

Abstract: Hypoxic blood-brain barrier (BBB) dysfunction is a common feature of CNS diseases however mechanisms underlying barrier disturbance are still largely unknown. This study investigated the role of transforming growth factor (TGF), a cytokine known to induce expression of the proprotein convertase Furin, in hypoxia-mediated barrier compromise.We show that exposure of brain endothelial cells (ECs) to hypoxia (1% O2) rapidly stimulates their migration. Additional exogenous TGF (0.4nM) exposure potentiated this effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…In light of the recent finding that TGF-b together with ab-crystallin is associated with EMT and with subretinal scarring (Ishikawa et al, 2016), simultaneous upregulation of both molecules could provide hints about the potential events that ultimately lead to fibrosis in angiogenic retinal diseases. Furthermore, it was recently demonstrated that myeloid cellderived furin, TGF-b activator, is crucial for the angiogenesis in OIR (Vähätupa et al, 2018b), but furin also aggravates hypoxiainduced blood-brain barrier dysfunction (Baumann et al, 2019). Taking together, the upregulation of proteins involved in mechanotransduction and actomyosin network as well as in the TGF-b signaling in OIR during the angiogenic phase may suggest that these processes could be important for angiogenesis, and thus provide a potential therapeutic target.…”
Section: Proteins Involved In Mechanotransduction Are Upregulated In mentioning
confidence: 99%
“…In light of the recent finding that TGF-b together with ab-crystallin is associated with EMT and with subretinal scarring (Ishikawa et al, 2016), simultaneous upregulation of both molecules could provide hints about the potential events that ultimately lead to fibrosis in angiogenic retinal diseases. Furthermore, it was recently demonstrated that myeloid cellderived furin, TGF-b activator, is crucial for the angiogenesis in OIR (Vähätupa et al, 2018b), but furin also aggravates hypoxiainduced blood-brain barrier dysfunction (Baumann et al, 2019). Taking together, the upregulation of proteins involved in mechanotransduction and actomyosin network as well as in the TGF-b signaling in OIR during the angiogenic phase may suggest that these processes could be important for angiogenesis, and thus provide a potential therapeutic target.…”
Section: Proteins Involved In Mechanotransduction Are Upregulated In mentioning
confidence: 99%
“…Furin is a ubiquitously expressed proprotein convertase implicated in many physiological and pathological processes ( 26 , 27 ). Studies report that it plays a critical role in the maturation of multiple proteins by cleavage at the specific proprotein recognition sequence RXK/RR and is overexpressed in different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial Na+ channel (ENaC), which could be active by furin, associates with increased blood pressure [14,21]. However, transforming growth factor (TGF-β) is also activated by furin but it contributes to lower blood pressure [22,23]. BNP activated by furin associates with low blood pressure through its diuretic and vasodilatory actions.…”
Section: Discussionmentioning
confidence: 99%